Two halves don't make a whole: Instability and idleness emerging from the co-evolution of the production and innovation processes - Patrick Llerena; Corentin Lobet; André Lorentz (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2024)
We propose a disaggregated representation of production using an agent-based fund-flow model that emphasizes inefficiencies, such as factor idleness and production instability, and allows us to explore their emergence through simulations. The model incorporates productivity dynamics (learning and depreciation) and is extended with time-saving process innovations. Specifically, we assume workers possess inherent creativity that flourishes during idle periods. The firm, rather than laying off idle workers, is assumed to harness this potential by involving them in the innovation process. Results show that a firm's organizational and managerial decisions, the temporal structure of the production system, the degree of workers' learning and forgetting, and the pace of innovation are critical factors influencing production efficiency in both the short and long term. The co-evolution of production and innovation processes emerges in our model through the two-sided effects of idleness: the loss of skills through forgetting and the deflection of time from the production of goods to the production of ideas giving birth to idleness-driven innovations. In doing so, it allows us to question the status of labour as an adjustment variable in a productive organisation. The paper concludes by discussing potential solutions to this issue and suggesting avenues for future research.
Keywords: D21; D24; D83; J24; L25; O31; O33; 330; Production Theory; Firm Theory; Agent-based model; Idleness; Innovation; Fund-flow